Laparoscopic versus open nephroureterectomy to treat localized and/or locally advanced upper tract urothelial carcinoma: oncological outcomes from a multicenter study. Issue 1 (December 2017) - Liu, Jian-Ye; Dai, Ying-Bo; Zhou, Fang-Jian; Long, Zhi; Li, Yong-Hong; Xie, Dan; Liu, Bin; Tang, Jin; Tan, Jing; Yao, Kun; He, Le-Ye
Abstract Background Many studies have reported the oncological outcomes between open radical nephroureterectomy (ONU) and laparoscopic radical nephroureterectomy (LNU) of upper tract urothelial carcinoma (UTUC). However, few data have focused on the oncological outcomes of LNU in the subgroup of localized and/or locally advanced UTUC (T1–4 /N0-X ). The purpose of this study was to compare the oncological outcomes of LNUvs . ONU for the treatment in patients with T1–4 /N0-X UTUC. Methods We collected and analyzed the data and clinical outcomes retrospectively for 265 patients who underwent radical nephroureterectomy for T1–4 /N0-X UTUC between April 2000 and April 2013 at two Chinese tertiary hospitals. Survival was estimated using the Kaplan-Meier method. Cox's proportional hazards model was used for univariate and multivariate analysis. Results The mean patient age was 62.0 years and the median follow-up was 60.0 months. Of the 265 patients, 213 (80.4%) underwent conventional ONU, and 52 (19.6%) patients underwent LNU. The groups differed significantly in their presence of previous hydronephrosis, presence of previous bladder urothelial carcinoma, and management of distal ureter (P  < 0.05). The predicted 5-year intravesical recurrence- free survival (RFS) (79%v s. 88%, P  = 0.204), overall RFS (47%v s. 59%, P  = 0.076), cancer-specific survival (CSS) (63%v s. 70%, P  = 0.186), and overall survival (OS) (61%v s. 55%, P  = 0.908) rates did not differ between the ONU and LNU groups. Multivariable Cox proportional regression analysis showed that surgical approach was not significantly associated with intravesical RFS (odds ratio [OR] 1.23, 95% confidence interval [CI] 0.46–3.65, P  = 0.622), Overall RFS (OR 0.99, 95% CI 0.54–1.83, P  = 0.974), CSS (OR 1.38, 95% CI 0.616–3.13, P  = 0.444), or OS (OR 1.61, 95% CI 0.81–3.17, P  = 0.17). Conclusions The results of this retrospective study showed no statistically significant differences in intravesical RFS, overall RFS, CSS, or OS between the laparoscopy and the open groups. Thus, LNU can be an alternative to the open procedure for T1–4 /N0-X UTUC. Further studies, including a multi-institutional, prospective study are required to confirm these findings.